Enhanced platelet MRP4 expression and correlation with platelet function in patients under chronic aspirin treatment - Massimi, Isabella; Lotti, Lavinia Vittoria; Temperilli, Flavia; Mancone, Massimo; Sardella, Gennaro; Calcagno, Simone; Turriziani, Ombretta; Frati, Luigi; Pulcinelli, Fabio M. (Thrombosis and Haemostasis, 2016)
Platelet multidrug resistance protein4 (MRP4)-overexpression has a role in reducing aspirin action. Aspirin in vivo treatment enhances platelet MRP4 expression and MRP4 mediated transport inhibition reduces platelet function and delays thrombus formation. The aim of our work was to verify whether MRP4 expression is enhanced in platelets obtained from patients under chronic aspirin treatment and whether it correlates with residual platelet reactivity. We evaluated changes on mRNA and protein-MRP4 expression and platelet aggregation in four populations: healthy volunteers (HV), aspirin-free control population (CTR), patients who started the treatment less than one month ago (ASA<1 month patients) and aspirinated patients who started the treatment more than two months ago (ASA>2 months patients). In platelets obtained from ASA>2 months patients, it was found a statistically significant MRP4 enhancement of both mRNA and protein expression compared to HV, CTR and ASA<1 month patients. Platelets obtained from ASA>2 months patients that present high levels of platelet MRP4, have higher serum TxB2 levels and collagen-induced platelet aggregation compared to patient with low levels of MRP4 in platelets. In addition collagen induced platelet aggregation is higher in in vitro aspirinated platelets obtained from patients with high levels of MRP4 patients compared to those obtained from patients with low MRP4 levels. We can assert that, in patients under chronic aspirin treatment, platelets that present high MRP4 levels have an increase of residual platelet reactivity, which is due in part to incomplete COX-1 inhibition, and in part to COX-1–independent mechanism.
Keywords: Platelet; MRP4; platelet aggregation; aspirin; gene expression